Liquid-phase assisted flash sintering of SiC from powder mixtures prepared by aqueous colloidal processing - Todd, R; Candelario, V; Moreno, R; Ortiz, A (Elsevier, 2016)
The effects were investigated of the starting particle size (i.e., nanometer or submicrometer powders), content of Y3Al5O12 additives (YAG; in the range 5–20 wt.%), and difference of size scales between the two particle types on the liquid-phase assisted flash sintering of SiC from powder mixtures prepared by aqueous colloidal processing. It was found that flash sintering benefits from the refinement of the particles size, the increase in additive content, and the smaller size scale of the particulate additive. It was also found that under the present flash sintering conditions (i.e., 900 °C furnace temperature, 13 A current, and 50 s in flash state) the resulting ceramics are, despite the formation of liquid phase, porous to a greater or lesser extent, and exhibit decreasing porosity gradients from their surface to the centre. These observations are rationalized to extract guidelines for powder batch design contributing to the pressureless ultrafast sintering of non-oxide advanced ceramics.